Role of Olive leaves Zinc Oxide Nanoparticles in Alleviating The Molecular and Histological Changes of Kidney in Female Goats-Induced by Gentamicin (Part III) - Al-ghareebaw, Aamir M.; Al-Okaily, Baraa N.; Ibrahim, Orooba M. S.; Mohammed, Ahmed D. (The Iraqi Journal of Veterinary Medicine, 2020)
This study aimed to investigate the protective influence of olive leave extract zinc oxide nanoparticles (OLEZnONPs) complex against gentamicin–induced kidney dysfunctions in goats. Twenty five adult female goats were randomly divided into five equal groups and treated as follows: control group (C) administered sterile distilled water (IM) for 10 days, group G administered 25 mg/kg BW gentamicin (IM) for 7 days, group Z administered 10 ìg/kg BW of OLEZnONPs (IP) for 3 days, group GTZ administered 25 mg/kg BW gentamicin (IM) for 7 days and then 10 ìg/kg BW of OLEZnONPs (IP) for 3 days, group GWZ administered 25 mg/kg BWs gentamicin (IM) and 10 ìg/kg BW of OLEZnONPs (IP) together for first 3 days and then followed by gentamicin only for 4 days. After seven days of the experiment, the gene expression of kidney injury molcule-1(KIM-1) and neutrophil gelatinase-association lipocalin (NGAL) gene expression of kidney tissue were measured. In addition, samples of kidney were obtained for histopathological examination. Gentamicin medication induced a marked elevation in kidney tissue KIM-1 and NGAL gene expression in G and GTZ groups compared to control and other groups. Intraperitoneal treatment of goats with OLEZnONPs did not significantly affect NGAL and KIM-1 gene expression in Z, GWZ, and control groups. Histologically, in contrast to control, gentamicin induced more extensive kidney damages such as necrotized glomeruli, atrophic glomeruli, and renal tubular epithelial necrosis, while it was found that these alterations in kidney tissues wereimproved in goats given OLEZnONPs with gentamicin compared to group G. In conclusion, our results demonstrate that OLEZnONPs reduce the deleterious effects of gentamicin with significantly decreasing of KIM-1 and NGAL gene expression and remodeling the histological changes of kidney in goats.